Soft drinks. Organoleptic analysis — a criterion for substantiation of expiry dates of products - E. M. Sevostyanova; O. A. Soboleva; I. L. Kovaleva; I. N. Gribkova (Пищевые системы, 2022)
The paper considers the topicality of the development of methodological approaches to the method for accelerated aging of soft drinks on the market. Selection principles for the controlled indicators that essentially influence finished product quality are presented and the method for sample processing that allows modeling conditions of product spoilage is examined. The investigations enabled establishing the most important criteria (acetaldehyde content, sucrose transformation, CO2 concentration, organoleptic indicators) that allow predicting expiry dates of soft drinks by express methods. The comparative assessment of quality and safety of soft drinks in the conditions of “accelerated” and “natural” aging (over the shelf life with regard to the reserve ratio) by the selected criteria was carried out. The criteria parameters for tasting assessment of soft drinks that allow more correct assessment of nuance descriptors of a product were developed. It is shown that cyclic impact of temperature regimes (warmth 50 °C / cold 6 °C) during the exposure time of 30 days enables modeling soft drink storage over the shelf-life of 12 months in the conditions of natural aging. In this study, the expiry date was confirmed for the studied soft drinks based on plant raw materials and was established for drinks based on flavoring agents.